Hubungan Lama Penggunaan Kontrasepsi Oral Kombinasi dengan Tekanan Darah pada Wanita Usia Subur - Mustiqa Febriniata; Widardo .; Ratih Puspita Febrinasari (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2012)
Background: Combined oral contraception is one of contraception methods that contains estrogen and progesterone. Both of that hormones have an effect on blood pressure levels because of the using duration of combined oral contraception, Body Mass Index (BMI), and acceptor age. The purpose of this research is to analyze the correlation between the using duration of combined oral contraception and blood pressure levels among fertile women in Jaten area, Karanganyar. Methods: This research used observational cross sectional analytic approach method. The population were fertile women who use combined oral contraception. The total sample were 48 patients who appropriate with inclusion and exclusion criterias. The data were collected by kuesioner, interview, anthropometry measurement, and blood pressure direct measurement. Those variables such as the using duration of combined oral contraception, blood pressure levels (systolic and diastolic), age, and body mass index (BMI) were analyzed using Kolmogorof-Smirnovs test of normality and linear regression analysis using SPSS 16 for Windows. Results: The result of simple statistic test using linear regression showed the correlation significancy between the using duration of combined oral contraception and blood pressure levels, both systolic (p=0,004) and diastolic (p=0,012). Conclusions: There is a correlation between the using duration of combined oral contraception and blood pressure levels among fertile women. Keywords: The using duration of combined oral contraception, Blood Pressure, Age, Body mass index